ANALISIS BASIS EKONOMI SEKTOR PERTANIAN DI KABUPATEN KARANGANYAR DENGAN PENDEKATAN ANALISIS LOCATION QUOTIENT - Sundari, Mei Tri; Setyowati, Nuning (Universitas Sebelas Maret, 2006)
This research aim to identify sector becoming base for economy in Karanganyar regency, identifying the position agricultural sector in economical sector in Karanganyar and identifying the sub sector of agriculture becoming base. The method used were the descriptive method along with Location Quotient (LQ) analysis method